A cycloaddition-rearrangement approach to the squalestatins - Hodgson, D; Bailey, J; Harrison, T (1996)
Reaction of diazodiketoester 4 with methyl glyoxylate in toluene in the presence of catalytic rhodium(II) acetate generates the 6,8- dioxabicyclo[3.2.1]octane 5 as a single regio- and stereo-isomer in good yield. Elaboration provides a suitable alcohol 7 for acid-catalysed rearrangement to give the 2,8-dioxabicyclo-[3.2.1]octane skeleton 8 of the squalestatins.